Microfluidic Chip for Site-Specific Neuropharmacological Treatment and Activity Probing of 3D Neuronal "Optonet" Cultures - Marom A.; Mahto S.K.; Shor E.; Tenenbaum-Katan J.; Sznitman J.; Shoham S. (My University, 2025)
The study introduces a "brain-on-a-chip" microfluidic platform that hosts brain-like 3D cultures ("optonets") whose activity and responses to flowing drugs are recorded optically. Optonets are viable, optically accessible 3D neural networks whose characteristics approximate cortical networks. The results demonstrate the ability to monitor complex 3D activity patterns during extended site-specific, reversible neuropharmacogical exposure, suggesting an interesting potential in drug screening. © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.